Assessing the Alkaline Phosphatase Levels as A Bone Biomarker in Gingival Crevicular Fluid during Semi-Rapid Expansion: Alkaline Phosphatase Levels in Gingival Crevicular Fluid during Expansion - Shamim, Ahmad; Shaheen, Asmi; Azeem, Muhammad; Atiq, Noman; Hussain, Shabbir; Mahmood, Shaker (Pakistan Journal of Health Sciences, 2025)
In orthodontics, the expansion of the maxilla is done to treat transverse maxillary deficiency in childhood. The cause of maxillary constriction may be genetic or environmental leading to crowding of teeth, cross bite and development of malocclusions. This expansion leads to increased maxillary dimensions. Objectives: To detect changes in alkaline phosphatase level as a bone biomarker in crevicular fluid during the phases of semi-rapid palatal expansion. Methods: Fifteen growing patients with an age range from 8-13 years were selected who needed maxillary semi-rapid palatal expansion as a part of orthodontic treatment. This quasi-experimental study was based on a non-probability purposive sampling technique conducted from August 2023 to July 2024. The samples were collected by inserting paper points in the gingival sulcus. The Periodontal status was evaluated before starting the sampling. The probing depths were recorded at different levels throughout the study until the completion of the retention period. The alkaline phosphatase levels in the gingival crevicular fluid were measured at buccal and palatal sites before, during and in the retention period after treatment. The alkaline phosphatase values were compared using the ANOVA test at different points in time with p<0.05 considered as statistically significant. Results: The ANOVA test showed a statistically significant increase in enzyme activity at different sites throughout maxillary semi-rapid palatal expansion treatment. Conclusions: It was concluded that the enzyme alkaline phosphatase as a biomarker is an indicator of active bone metabolism in growing children while going through the maxillary semi-rapid palatal expansion treatment.